14-Deoxyxyloccensin K from Chisocheton ceramicus (Meliaceae) - Najmuldeen, I.A.; Hadi, A.H.A.; Awang, K.; Mohamad, K.; Ng, S.W. (International Union of Crystallography, 2010)
The title limonoid 14-deoxyxyloccensin K, C(27)H(34)O(7), isolated from Chisocheton ceramicus (Meliaceae), features an oxygen linkage between carbon-3 and carbon-8 along with a tetrahydrofuryl sub-unit. The six-membered rings adopt chair configurations and the tetrahydrofuryl sub-unit has an envelope shape.